LYTHRUM SALICARIA (LYTHRACEAE), NUEVA CITA PARA LA FLORA DE ARGENTINA - Torres, Cristian D. (2015)
Fil: Torres, Cristian D. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche; Argentina